Women's Perspectives on Career in Family and Community Environment - Uswatun Hasanah Harahap; Mizanul Hasanah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This article begins with the writer's anxiety about society's thinking about the functions and duties of women currently. Not only society, but even families among women also highlight the changes in women today. Intense competition in a career today is different from the past. Many men take on career roles and work outside the home. However, over time the need for talented people is not just looking at gender. Now, women can take on any role that men can play. The question is what about society's view of women with careers. Especially women who are married but still have a career. This study aims to determine how the perspective of women who have a career towards their families and surrounding communities. The research method used is descriptive qualitative with a case study approach. The instrument used is a direct interview with the researcher with the resource person. This study focused on one family in North Sumatra. The results of the study show that inequality in society is unavoidable. However, the importance of the role of the family in understanding the changing times and the support and cooperation to understand each other's functions and roles of women in careers.